ABOUT ORGANIZING AND CONDUCTING THE MEASURES OF PREVENTING SEVERE ACUTE RESPIRATORY SYNDROME IN NOVOSIBIRSK REGION - V. N. Mikhejev; L. K. Ivanova; A. P. Fedyanin (Acta Biomedica Scientifica, 2020)
Clinic-and-epidemiological characteristics of suspected «atypical pneumonia» cases detected in NovosibirskRegion, organizing of early detection of ill persons and their hospitalizing are presented. Main organizing-methodical and administrative-ordering measures directed on preventing of SARS delivery and spreading on the territory of Region are reflected.The organizational measures for preventing of «atypical pneumonia» allowed to avert its delivery and spreading in the Region, and to conduct the complex of treatment-and-diagnosis and anti-epidemic measures in suspected SARS cases.